2003
DOI: 10.1161/01.cir.0000087446.53440.a3
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Aortic Valve Surgery in the Elderly: A Case-Control Study

Abstract: Introduction-Although minimally invasive aortic valve surgery (MIAVR) is performed in many centers, few studies have compared its results to a standard sternotomy (SS) approach. We assessed the hypothesis that, when compared with SS in the elderly population, MIAVR has similar morbidity and mortality and allows faster hospital recovery. Methods and Results-From

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 37 publications
2
60
1
1
Order By: Relevance
“…[14e16] two studies were propensity matched [13,17] and one case control [12]. One study [14] reported amalgamated primary and secondary outcomes for minimally invasive mitral and aortic hence could not be included in the subgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[14e16] two studies were propensity matched [13,17] and one case control [12]. One study [14] reported amalgamated primary and secondary outcomes for minimally invasive mitral and aortic hence could not be included in the subgroup analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies [12,16,17] included specifically minimally invasive aortic valve and two studies [13,15] minimally invasive mitral surgery valve and were meta-analyzed separately. One study [14] did not separate outcomes therefore was not part of the subgroup analysis.…”
Section: Subgroup and Quality Scoring Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…No difference in all-cause mortality has been identified between SAVR and TAVR (9,10,24,25). MiniAVR is a second option for minimally invasive management of AS and has been shown to be equivalent to and possibly better than SAVR in terms of morbidity and mortality, while decreasing blood loss, ICU and hospital length of stays and recovery time (13,19,(26)(27)(28). The main drawback is the technical difficulty and prolonged AXC and CPB times.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of minimally invasive aortic valve replacement with traditional median sternotomy technique indicated similar hospital mortality (6.9%) and morbidity (18%), with comparable actuarial survival at 3 years (85%). Furthermore, the minimal surgical approach resulted in a shorter length of stay, with a greater proportion of patients able to be discharged in a case-matched study [8].…”
mentioning
confidence: 95%